АТРОФ ТАБИИЙ МУҲИТНИ РАДИАКТИВ МОДДАЛАР БИЛАН БОҒЛИҚ ЧИҚИНДИЛАРНИНГ САЛБИЙ ТАЪСИРЛАРИДАН ҲУҚУҚИЙ МУҲОФАЗА ҚИЛИШ - Бабаназаров, К.Р.; Кутлымуратов, Ф.К. (SCIENCE and SOCIETY, 2016)
The article is devoted to the questions of legal protection of environment from the radiation substances connected with radioactive waste. The author of the article also studies the mechanisms of action of domestic acts in this sphere.